Care of (potentially) brain‐dead patients: A qualitative study protocol. (31st July 2019) - Drexler, Sabine; Kugler, Christiane; Farin, Erik
Abstract: Aim: Aim of this study was to describe the experiences of intensive care unit (ICU) nurses, physicians and relatives of (potentially) brain dead patients; and to develop recommendations to optimize the workflows on ICUs. Background: Limited published information on caring for brain dead patients suggest it to be a burden for the nursing staff. It also remains unclear how physicians and relatives of (potentially) brain dead patients perceive these experiences. Design: Interpretive phenomenology according to Benner. Methods: Medical caregivers (nurses' und physicians) from multiple wards in a German University Medical Center and relatives of (potentially) brain dead patients will be interviewed. Data collection will include episodic interviews with participants' experiences in care of (potentially) brain dead patients. The study is funded by the Ministry of Science, Research and the Arts, Baden‐Württemberg (1 February 2016). Discussion: Gaining insights into caring for (potentially) brain dead patients and its associated burden will lead to the development of better recommendations to assist all people involved. Impact: Expand the understanding of the experience of healthcare professionals in the care for (potentially) brain dead patients. Understand the experience of relatives of (potentially) brain dead patients. Findings from this study will support the development of recommendations for action by a multi‐professional expert group consisting of nurses, physicians, healthcare managers and patient advocates. Trial registration: Protocol version. German Register for Clinical Studies (Registration No. DRKS00010420) Database of Health Services Research Germany (Project Nr. VfD_16_003710). Abstract : 目的: 本研究的目的是描述重症监护病房(ICU)护士、医生和(潜在)脑死亡患者亲属的经验, 并提出优化重症监护病房工作流程的建议。 背景: 关于照顾脑死亡患者的公开信息很有限, 意味着这对护理人员来说是一种负担。目前尚不清楚(潜在的)脑死亡患者的医生和亲属是如何看待这些经历的。 设计: 本纳的解释现象学。 方法: 来自德国大学医学中心多个病房的医护人员(护士和医生)和(潜在)脑死亡患者的亲属将接受采访。研究将收集包括对参与者在(潜在的)脑死亡患者护理方面的经验的阶段性访谈数据。本研究由巴登‐符腾堡州科学艺术研究部资助(2016年2月1日)。 讨论: 深入了解(潜在的)脑死亡患者的护理方式及其相关负担有助于提出更好的正式建议, 以帮助所有相关人员。 影响: 这项研究将扩大医疗保健专业人员对(潜在)脑死亡患者护理经验的理解, 使其了解(潜在)脑死亡患者亲属的经历。这项研究的结果将作为由护士、医生、医疗保健经理和患者倡导者组成的多专业专家组制定行动建议的参考。 试验注册号: 协议版本号。德国临床研究注册中心(注册号:DRKS00010420)德国卫生服务研究数据库(项目编号:VFD U 16 U 003710)。